Pendidikan Kristiani sebagai Sarana Pembentukan Spiritualitas Generasi Milenial: Christian Education as a Tool for Spiritual Formation in the Millennial Generation - Yornan Masinambow; Yosef Nasrani (Sekolah Tinggi Teologi Baptis Indonesia, 2021)
This study aims to describe the importance of Christian education to form the spirituality of the millennial generation. Presented using a qualitative-descriptive approach with the support of literature studies. The conclusion is the Christian education is a vital tool that can shape the spirituality of the millennial generation. The Christian education style praises this goal is the relationship of friendship and love for others in the learning process by families, churches, and schools.